2022
DOI: 10.5194/essd-14-1795-2022
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-production processes increasingly dominate greenhouse gas emissions from agri-food systems

Abstract: Abstract. We present results from the FAOSTAT emissions shares database, covering emissions from agri-food systems and their shares to total anthropogenic emissions for 196 countries and 40 territories for the period 1990–2019. We find that in 2019, global agri-food system emissions were 16.5 (95 %; CI range: 11–22) billion metric tonnes (Gt CO2 eq. yr−1), corresponding to 31 % (range: 19 %–43 %) of total anthropogenic emissions. Of the agri-food system total, global emissions within the farm gate – from crop … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 32 publications
2
41
0
3
Order By: Relevance
“…1 ). This estimate is consistent with the emissions range of recent estimates covering the same period (9–22 GtCO 2 e/y) 3 , 6 , 16 , 18 , 20 22 . Four value-chains–beef, milk, rice and maize–are responsible for nearly 65% (13.9 GtCO 2 e) of total FS emissions, and seven value-chains (+ wheat, pig and poultry) are responsible for almost 80% of emissions (17.2 GtCO 2 e).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…1 ). This estimate is consistent with the emissions range of recent estimates covering the same period (9–22 GtCO 2 e/y) 3 , 6 , 16 , 18 , 20 22 . Four value-chains–beef, milk, rice and maize–are responsible for nearly 65% (13.9 GtCO 2 e) of total FS emissions, and seven value-chains (+ wheat, pig and poultry) are responsible for almost 80% of emissions (17.2 GtCO 2 e).…”
Section: Resultssupporting
confidence: 90%
“…1 ). Close to 70% of FS emissions come from land-use change and farming activities 6 , 16 .
Figure 1 Global food systems emissions in 2020 ( A ) and estimated global food systems emissions 2010–2050 ( B ).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, GHG emission factors of a biological technology obtained from references are not representative for real emission factors of all WWTPs with the same technology. (3) GHG emissions from industrial WWTPs are not available and thus not included in our study although being important GHG emission sources of wastewater treatment systems [52][53][54] . For instance, Xing et al reported that CH 4 emissions from on-site industrial wastewater treatment were always higher than that of domestic wastewater treatment between 2003 and 2008 in China.…”
Section: Limitationsmentioning
confidence: 99%
“…That said, post farm emissions (e.g. from energy use in food processing, food transport, food storage, cooking) have been rising substantially in recent years, requiring a rethink of mitigation strategies for the food sector (11). A look across the whole food system therefore becomes important for finding the biggest levers of change.…”
mentioning
confidence: 99%